Tunical vaginalis excision: the hydrocelectomy technique not to be forgotten (Tanzania Medical Journal, 2007)
Background: The technique of excising the hydrocele sac (tunica vaginalis) rather extensively, leaving only 1- 2 cm rim of tissue adjacent to the testis and epididymis in the treatment of hydrocele in adults is to be advocated, as it gives the same result as Jaboulay's technique. The advantage with this technique is that, it reduces the size of the remaining tissue to near normal postoperatively and no risk of strangulating the spermatic cord as it may happen in Jaboulay,s technique. Methods: Adult male patients with different sizes of hydroceles were seen, investigated and operated with this technique in three hospitals- Muhimbili National hospital, Tumaini and MHS- Massana hospitals between January 2004 and June 2006. Results: A total of 25 patients were operated using this technique. The age ranged between 20 - > 60years. Most of them had right-sided idiopathic hydrocele, the technique provided excellent results in the treatment of such conditions. Conclusion: The technique of excising the hydrocele sac (tunica vaginalis) needs to be advocated and should not be forgotten hydrocelectomy techniques.. Tanzania Medical Journal Vol. 21 (1) 2006: pp. 20-21